Manajemen Komunikasi dalam Mengatasi Hambatan Komunikasi Transmigran Jawa di Daerah Tujuan - M Fikri Akbar; Damayanti; Noning Verawati (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2026)
This study aims to analyze the role of communication management in overcoming communication barriers experienced by Javanese transmigrants in destination areas, particularly in Lampung Province. The identified barriers are multidimensional, including language differences, cultural gaps, limited access to information, and psychological factors. These barriers have the potential to hinder social integration and the success of the transmigration program if not managed systematically. The research employs a qualitative approach with a phenomenological method to explore the subjective experiences of transmigrants. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed using thematic techniques. The findings reveal that communication management, which includes planning, organizing, implementing, and controlling stages, effectively reduces communication barriers. Strategies applied involve designing messages based on local wisdom, forming social groups as interaction media, implementing participatory communication through village forums and digital platforms, and controlling through monitoring and evaluation. These strategies positively impact increased transmigrant participation, reduced social conflicts, strengthened economic cooperation, and improved self-confidence among transmigrants. This study contributes scientifically to the development of communication for development and intercultural communication, offering a communication management model based on local wisdom that can be adapted to other transmigration areas. The findings are expected to serve as a reference for policymakers and communication practitioners in designing inclusive and sustainable communication strategies.